2013
DOI: 10.1109/tvcg.2013.153
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Guidance on Scatterplot and Dimension Reduction Technique Choices

Abstract: To verify cluster separation in high-dimensional data, analysts often reduce the data with a dimension reduction (DR) technique, and then visualize it with 2D Scatterplots, interactive 3D Scatterplots, or Scatterplot Matrices (SPLOMs). With the goal of providing guidance between these visual encoding choices, we conducted an empirical data study in which two human coders manually inspected a broad set of 816 scatterplots derived from 75 datasets, 4 DR techniques, and the 3 previously mentioned scatterplot tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 38 publications
5
122
0
Order By: Relevance
“…These design factors were consistent with the scagnostics (aspects of scattered points, such as outlier, shape, trend, density, and coherence) defined by Wilkinson et al [5]. A follow-up study [17] indicated that a 2D scatterplot is as good as an interactive 3D scatterplot or a scatterplot matrix in showing classes. Gleigher et al [18] explored the visual design of multiclass scatterplots for the task of identifying the mean value of a set of points.…”
Section: Empirical Studies Of Scatterplot Perceptionsupporting
confidence: 80%
“…These design factors were consistent with the scagnostics (aspects of scattered points, such as outlier, shape, trend, density, and coherence) defined by Wilkinson et al [5]. A follow-up study [17] indicated that a 2D scatterplot is as good as an interactive 3D scatterplot or a scatterplot matrix in showing classes. Gleigher et al [18] explored the visual design of multiclass scatterplots for the task of identifying the mean value of a set of points.…”
Section: Empirical Studies Of Scatterplot Perceptionsupporting
confidence: 80%
“…This conclusion was also stated by Sedlmair [45], in the sense that no single dimensionality reduction technique can be considered superior to all others, and some techniques may not reveal certain structures in real world data sets. Moreover, we observe that the projections tend to perform better on document data.…”
Section: Resultsmentioning
confidence: 77%
“…In-depth investigation of effectiveness, however, goes beyond the scope of this paper. Previous work has shown that assessing effectiveness of interactive DR solutions depends heavily on context factors, such as users, data, domain, and tasks at hand [50,52]. A generic comparison of the scenarios' usefulness and effectiveness is thus a non-trivial endeavor, and further work is needed.…”
Section: S6 Defining Constraintsmentioning
confidence: 99%